2010
DOI: 10.1370/afm.1136
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Electronic Health Record Implementation: New Insights on Physician and Patient Adaptation

Abstract: PURPOSE Although there is signifi cant interest in implementation of electronic health records (EHRs), limited data have been published in the United States about how physicians, staff, and patients adapt to this implementation process. The purpose of this research was to examine the effects of EHR implementation, especially regarding physician-patient communication and behaviors and patients' responses. METHODSWe undertook a 22-month, triangulation design, mixed methods study of gradual EHR implementation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 36 publications
0
49
1
2
Order By: Relevance
“…Seven studies examined both patient perceptions and observed behaviors. 30,31,43,44,48,49,55 Only two studies were interventional in nature. 61,70 Forty-seven of the 53 studies were published after the year 2000, and 19 (35.8 %) were published since 2011.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies examined both patient perceptions and observed behaviors. 30,31,43,44,48,49,55 Only two studies were interventional in nature. 61,70 Forty-seven of the 53 studies were published after the year 2000, and 19 (35.8 %) were published since 2011.…”
Section: Resultsmentioning
confidence: 99%
“…While 11 studies [29][30][31]34,37,38,43,44,48,49,55 attempted to correlate objective observations of communication behaviors with patient perceptions of care, only seven of these studies elicited patient perspectives directly. 30,31,43,44,48,49,55 The remaining studies used researcher perceptions of the patient perspective as a proxy.…”
Section: Correlating Emr Communication Behaviors With Patient Perceptmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Shield et al, 11 in which residency clinic patients maintained strong trust in the doctor-patient relationship during EHR implementation, convinced one reader that, "if the verdict was not in, it is now. The benefi ts of EHR far outweigh the various costs associated with their implementation."…”
Section: Technology Chronic Care and Organizational Ethicsmentioning
confidence: 99%
“…T his issue of the Annals addresses ethical issues, 1,2 the effects of implementing new models of care support, 3,4 prevention, 5 screening, 6-8 and patients' health information-seeking behaviors. 9 It closes with a new approach for calculating the complexity of patient visits 10,11 and a community celebration of the life of a personal physician.…”
mentioning
confidence: 99%